Hemostatic Genes Exhibit a High Degree of Allele-Specific Regulation in Liver - Olsson Lindvall, Martina; Hansson, Lena; Klasson, Sofia; Davila Lopez, Marcela; Jern, Christina; Stanne, Tara M. (Thrombosis and Haemostasis, 2019)
Objective Elucidating the genetic basis underlying hepatic hemostatic gene expression variability may contribute to unraveling genetic factors contributing to thrombotic or bleeding disorders. We aimed to identify novel cis-regulatory variants involved in regulating hemostatic genes by analyzing allele-specific expression (ASE) in human liver samples.Study Design Biopsies of human liver tissue and blood were collected from adults undergoing liver surgery at the Sahlgrenska University Hospital (n = 20). Genomic deoxyribonucleic acid (gDNA) and total ribonucleic acid (RNA) were isolated. A targeted approach was used to enrich and sequence 35 hemostatic genes for single nucleotide polymorphism (SNP) analysis (gDNAseq) and construct individualized genomes for transcript alignment. The allelic ratio of transcripts from targeted RNAseq was determined via ASE analysis. Public expression quantitative trait loci (eQTL) and genome-wide association study (GWAS) data were used to assess novelty and importance of the ASE SNPs (and proxies, r2 ≥ 0.8) for relevant traits/diseases.Results Sixty percent of the genes studied showed allelic imbalance across 53 SNPs. Of these, 7 SNPs were previously validated in liver eQTL studies. For 32 with eQTLs in other cell/tissue types, this is the first time genotype-specific expression is demonstrated in liver, and for 14 ASE SNPs, this is the first ever reported genotype–expression association. A total of 29 ASE SNPs were previously associated with the respective plasma protein levels and 17 ASE SNPs to other relevant GWAS traits including venous thromboembolism, coronary artery disease, and stroke.Conclusion Our study provides a comprehensive ASE analysis of hemostatic genes and insights into the regulation of hemostatic genes in human liver.
Keywords: coagulation factors; gene regulation; hemostasis; single nucleotide polymorphisms; thrombosis